PENERAPAN METODE EKSPRESI BEBAS UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN SENI PATUNG DI KELAS IX-5 SMP NEGERI 1 TIGAPANAH - SANTA BR KARO (LP2MTBM MAKARIOZ, 2018)
This study aims to improve the quality of sculpture learning through the method of free expression in class IX-5 SMP Negeri 1 Tigapanah academic year 2017/2018. This study is a classroom action research with two cycles consisting of four stages: planning, action, observation and reflection. The subjects of the study were the students of class IX-5 SMP Negeri 1 Tigapanah in the 2017/2018 school year as many as 35 students. The research instrument used is observation sheet of student activity, observation sheet of learning management and sculpture skill test instrument. The results showed that free expression method was able to improve the quality of sculpture learning in class IX-5 of SMP Negeri 1 Tigapanah in the academic year 2017/2018 with improved learning management achieving good quality in every aspect of observation and the percentage of student activeness increased from 74% to 89% while the percentage of mastery of sculpture skills rose from 74% to 86%. So in the second cycle of activity and student completeness has exceeded the research success criteria by 85%.